ELECTRONIC EDUCATION BASED ON MOBILE TECHNOLOGIES CREATING RESOURCES - Maksimova Tatyana Leonidovna (Journals Park Publishing, 2022)
This article is about e-learning based on mobile technologies extensive information on resource creation, mobile education, mobile opportunities and conveniences of education. Global Trends Analysis Education from mobile technologies to solve various pedagogical tasks in the process demonstrates the enormous vital importance of use. The article also discusses e-learning based on mobile technologies resource creation technology, mobile book creation software, mobile there are several ways to use the device for educational purposes listed.